The Environmental Education Foundation, Another Endeavor by Mario Boza-Loría (Biocenosis, 2022)
This is a synopsis of the main environmental education actions developed by the Environmental Education Foundation during its administration. Mario Boza-Loria created this non-profit organization with the support of people who, like him, were visionaries in the environmental field. They decided to join efforts to raise awareness in Costa Rican society, promoting an environmental culture oriented to the conservation of protected wildlife areas and active participation in the solution of the country's environmental problems.
Keywords: Environmental Education Foundation; environmental education; environmental problems; awareness; training